Controlled traffic farming delivers improved agronomic performance of wheat as a result of enhanced rainfall and fertiliser nitrogen use efficiency. (4th July 2021) - Hussein, Mahmood A.; Antille, Diogenes L.; Kodur, Shreevatsa; Chen, Guangnan; Tullberg, Jeff N.
ABSTRACT: This study investigated the agronomic response and economic return of wheat grown in compacted and non-compacted soils to represent the conditions of non-controlled (non-CTF) and controlled traffic (CTF) systems, respectively. Yield-to-nitrogen responses were derived after application of urea, DMPP-treated urea, and UAN at rates between 0 and 300 kg ha −1 N. Soil properties were measured to guide parametrisation of APSIM, which was used to assess long-term (50 years) effects of CTF and non-CTF soil conditions on crop productivity, rainfall-use efficiency (RUE) and surface runoff. Grain yield and yield components were significantly higher in CTF compared with non-CTF. When N inputs were optimised, N use efficiency (NUE) was more than double in CTF (≈23%) compared with non-CTF (≈9%). RUE was about 15% higher in CTF, which concurrently reduced the amount of surface runoff compared with non-CTF. For years with average rainfall (240-mm in-crop), yield penalties of up 12% may be expected in non-CTF. APSIM simulations showed that increased productivity, and inter-annual yield stability, can increase gross margin of wheat by AUD30-50 ha −1 depending on in-crop rainfall and the tillage method used. In non-CTF systems, improvements in NUE and RUE are constrained by soil compaction. Enhanced efficiency fertilizers cannot compensate for other stresses caused by compaction and therefore cannot achieve the same NUE and RUE as the CTF system. Adoption of CTF in water-constrained environments improves profitability and resource-use efficiency.